2020
DOI: 10.1177/1059840520975745
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Transition in School-Based Health Centers: A Pilot Study

Abstract: Nationally, there are low rates of high school–age youth receiving health care transition (HCT) preparation from health care providers. This pilot study implemented and assessed the use of a structured HCT process, the Six Core Elements of HCT, in two school-based health centers (SBHCs) in Washington, DC. The pilot study examined the feasibility of incorporating the Six Core Elements into routine care and identified self-care skill gaps among students. Quality improvement methods were used to customize, implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Pediatric oncology and survivor programs should consider implementing health system supports to prepare survivors for healthcare transition and, if applicable, eventual transfer to adult-centered care. The US Center for Health Care Transition Improvement offers guides to assist clinicians and health systems in assessing their healthcare transition activities and implementing the six core elements of Health Care Transition [ 33 ] [ https://www.gottransition.org/six-core-elements/ ]. These guides offer frameworks for supporting the transition to adult-centered care with or without a change in survivor care provider; thus, they are applicable regardless of whether or not institutions transfer survivors out for long-term follow-up care in adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pediatric oncology and survivor programs should consider implementing health system supports to prepare survivors for healthcare transition and, if applicable, eventual transfer to adult-centered care. The US Center for Health Care Transition Improvement offers guides to assist clinicians and health systems in assessing their healthcare transition activities and implementing the six core elements of Health Care Transition [ 33 ] [ https://www.gottransition.org/six-core-elements/ ]. These guides offer frameworks for supporting the transition to adult-centered care with or without a change in survivor care provider; thus, they are applicable regardless of whether or not institutions transfer survivors out for long-term follow-up care in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest COG programs are most in need of developing written transition policies (Core Element 1 — Transition and Care Policy/Guide), adopting transition readiness tools (Core Element 3 — Transition Readiness), and establishing mechanisms to obtain feedback from young adult survivors about their transition process (Core Element 6 — Transfer Completion). Considerations for developing transition policies and eliciting elicit feedback from survivors on their experience with the transition process can be found on the Got Transition® website, along with sample policies and example feedback surveys [ 33 ]. Systematic reviews of health transition assessment tools [ 34 , 35 ] have identified several measures that can be used to evaluate transition readiness, including the Transition Readiness Assessment Questionnaire (TRAQ) [ 36 , 37 ], TRxANSITION Index [ 38 ], Self-management and Transition to Adulthood with Rx = treatment (STARx) [ 39 ], Readiness for Transition Questionnaire (RTQ) [ 40 – 42 ], Transition Q [ 43 ], and the California Healthy and Ready to Work Transition Assessment Tool (HRTW) [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…− Leverage existing Internet resources (ie, gottransition.org 33 ), the electronic health record, telehealth, and smartphones to provide materials to patients, parents, and providers − Create regional and national transition networks of pediatric and adult SBS providers developmental and neurocognitive delays may affect an AYA's ability to perform some or all of these tasks. For patients who will be unable to function independently in the adult care setting, the transition process and education should be targeted toward caregivers.…”
Section: Resourcefulmentioning
confidence: 99%
“…Geography may play a role in the strength of these partnerships, and the success of transition programs within the same medical center should be compared to those that refer patients to outside centers. That said, survival measures for pediatric heart transplant recipients did not vary according to distance from the transplanting center (64). Similarly, travel time did not result in impactful delays in receipt of care or outcomes for pediatric patients undergoing particle beam therapy for medulloblastoma (65).…”
Section: Additional Considerationsmentioning
confidence: 99%